ANALISIS GAYA BAHASA PADA CERPEN “PERMINTAAN TERAKHIR” KARYA USMAR ISMAIL - Ignatius Dimas Adi Suarjaya; Dewi, Novita (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Language is one of the important aspects that need to be researched. The language that a person uses can be conveyed orally or in writing. One of the forms of language used in writing can be found in the form of literary works. Literary works are often used as tools or media to be studied in more depth related to the structure and content in the literary work. The purpose of this study was to determine the linguistic characteristics used by Oesmar Ismail in his short story entitled